2022 Design, Automation &Amp; Test in Europe Conference &Amp; Exhibition (DATE) 2022
DOI: 10.23919/date54114.2022.9774735
|View full text |Cite
|
Sign up to set email alerts
|

Reliability Analysis of FinFET-Based SRAM PUFs for 16nm, 14nm, and 7nm Technology Nodes

Abstract: SRAM Physical Unclonable Functions (PUFs) are among other things today commercially used for secure primitives such as key generation and authentication. The quality of the PUFs and hence the security primitives, depends on intrinsic variations which are technology dependent. Therefore, to sustain the commercial usage of PUFs for cutting-edge technologies, it is important to properly model and evaluate their reliability. In this work, we evaluate the SRAM PUF reliability using within class Hamming distance (WC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…But it subsequently leads to less noise in highperformance SRAM PUFs as compared to LP (Low performance) SRAM PUFs. Highperformance SRAM PUF designs exhibit significantly reduced Hamming distance, ranging from 1 to 3 percent, in contrast to the 6 to 12 percent found in low-performance (LP) designs [13]. However, in [14], the authors showed that the impact of temperature on static behavior of HP SRAM PUFs is higher than LP SRAM PUFs.…”
Section: Existing Literature: Sram Puf Reliabilitymentioning
confidence: 96%
“…But it subsequently leads to less noise in highperformance SRAM PUFs as compared to LP (Low performance) SRAM PUFs. Highperformance SRAM PUF designs exhibit significantly reduced Hamming distance, ranging from 1 to 3 percent, in contrast to the 6 to 12 percent found in low-performance (LP) designs [13]. However, in [14], the authors showed that the impact of temperature on static behavior of HP SRAM PUFs is higher than LP SRAM PUFs.…”
Section: Existing Literature: Sram Puf Reliabilitymentioning
confidence: 96%